THE STRUCTURAL POSITION OF THRUSTS IN THE RECENT OROGEN OF THE CENTRAL TIEN SHAN - Mikolaichuk A.V. (My University, 2000)
The results of close mapping of areas of recent thrusts in the Central Tien Shan demonstrate that they are an element of intricately built shear zones. A system of conjugate diagonal faults of NW and NE strikes which are secondary with respect to the marginal ones develops within sublatitudinal blocks bordered by sinistral reverse faults and strike-slip faults. Mass motion along the system of conjugate faults brings about local compression zones in the apices of wedge-like blocks. In the natural geologic structure, these zones are compensated by major reverse faults and thrusts. When the thrusts came out to the surface, the frontal part of the allochthon was destroyed, which is marked by Neogene-Early Pleistocene tectonic gravitational mixtites. The described structure of the shear zones formed in a transpression setting.
Keywords: Neogene; Pleistocene; Кайнозой::Неоген; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene; Кайнозой::Четвертичная::Плейстоцен